LARVICIDAL ACTIVITY OF METHANOL EXTRACT OF NEIUM OLEANDER AND TRIGONELLA FOENUM AGAINST CLUEX MOSQUITO LARVAE, ALONGWITH A SURVEY OF ENTIRE VELLORE DISTRICT FOR MOSQUITO - MADHURI.P; LOKESH.R; REVATHY.A.R (International Journal of Pharma and Bio Sciences, 2013)
The aim of the study is to test the Larvicidal activity of methanol extract of Nerium Oleander and Trigonella Foenum, individually and in combination. Then to compare the result with the result obtained from the previous study with the aqueous extract of the same plants. A survey within Vellore district was done to check for the distribution and population of genera present. The study was done only on Culex genera, due to its vast availability, due to the level of tolerance it demonstrated against the aqueous extract and also due to level of threat this genera posses for the public. The results obtained from Larvicidal assay with the methanol extract is considerably higher than the aqueous extract, though with a disappointment that the combination of Nerium oleander and Trigonella foenum methanol extract did not provide a drastic scale up, as it did with the combination of aqueous extract.